2009
DOI: 10.1021/np900230p
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Xanthohumol and Functional Impact on Hepatic Ischemia−Reperfusion Injury

Abstract: Therapeutic effects of dietary flavonoids have been attributed mainly to their antioxidant capacity. Xanthohumol (1), a prominent flavonoid of the hop plant, Humulus lupulus, was investigated for its antioxidant potential and for its effect on NF-κB activation. To examine the biological relevance of 1, a hepatic ischemia/reperfusion model was chosen as a widely accepted model of oxidative stress generation. The impact of 1 on endogenous antioxidant systems, on the NF-κB signal transduction pathway as well as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
(106 reference statements)
3
21
1
1
Order By: Relevance
“…This leads to release of mitochondrial cytochrome c and activates caspase-9 which, in turn, activates caspase 3, the initiator of the final execution stages of nuclear apoptosis [24]. These results are in accordance with those obtained by Hartkorn et al, [25], who observed decreased expression of the antiapoptotic gene Bcl-xL following hepatic ischemia in rat liver and attributed this to the suppressing effect of released ROS.…”
Section: Discussionsupporting
confidence: 91%
“…This leads to release of mitochondrial cytochrome c and activates caspase-9 which, in turn, activates caspase 3, the initiator of the final execution stages of nuclear apoptosis [24]. These results are in accordance with those obtained by Hartkorn et al, [25], who observed decreased expression of the antiapoptotic gene Bcl-xL following hepatic ischemia in rat liver and attributed this to the suppressing effect of released ROS.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our results, Hartkorn et al [14] reported decreased expression of the antiapoptotic gene Bcl-xL following hepatic ischemia in rat liver and attributed this to the suppressing effect of the released reactive oxygen species (ROS).…”
Section: Discussionsupporting
confidence: 93%
“…These compounds are vital ingredients in the brewing industry as a source of bitter flavor, herbal aromas, and natural preservative. Nevertheless, the secondary metabolites of the hop has a long history of utilization for medicinal purposes due to their diverse bioactivities, such as anti-carcinogenic [1], antiinflammatory [2], antimicrobials [3], antioxidant [4], antiglycemic [5], neuroprotective [6], anxiolytic, and sedative effects [7]. In addition to cones, the glandular trichomes are present in lower density on the lower leaf epidermis ( Figure 1A), differ morphologically from those present in cones [8], contain low but detectable levels of hop acids, terpenes, xanthohumol and flavonols and serve as the primary site of trichome-specific secondary metabolite biosynthesis [9].…”
Section: Introductionmentioning
confidence: 99%